Hydrocarbon Gases in Seafloor Sediments of the Edge Shelf Zone of the East Siberian Sea and Adjacent Part of the Arctic Ocean - Yatsuk, Andrey; Gresov, Alexander; Snyder, Glen Tritch (Frontiers in Earth Science, 2022)
The continental margins of the East Siberian Sea and Arctic Ocean are among the Earth’s most inaccessible marine environments for hydrocarbon research, due to the almost year-round presence of ice cover. Despite this, limited preliminary assessments which have been carried out to date have all yielded some indication of the high oil and gas production potential for these regions. This article presents the results of gas-geochemical studies of seafloor sediments of East Siberian Sea, obtained in three expeditions onboard the R/V “Akademik Lavrentiev” in 2008 (LV45), 2016 (LV77) and 2020 (LV90). The composition of sorbed hydrocarbon gases in seafloor sediments was analyzed. In addition, the stable isotopic composition of carbon was determined for CH4, C2H6, and CO2 in gases which were desorbed from the marine sediments. The sediments were also analyzed for organic matter content. Despite the absence of observable gas seepage directly into the water column, at some stations increased concentrations of methane and hydrocarbon gases were encountered, indicating the widespread predominance of thermogenically derived gases. We present a hydrocarbon classification system which delineates eight identifiable sources of regional gas occurances (coal-gas, igneous rocks, solid bitumen, condensate-gas, gas-condensate, oil-gas, gas-oil and oil gases). Stable isotope analysis of carbon in CH4, C2H6 and CO2 indicates varying degrees of mixing between a shallow, early-kerogen gas source and a deeper mantle carbon source in some areas of the study.